2014
DOI: 10.3357/asem.3828.2014
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Gravitational Stress on Normovolemic and Hypovolemic Men and Women

Abstract: Background Earth based simulations of physiologic responses to space mission activities are needed to develop prospective countermeasures. To determine whether upright lower body positive pressure (LBPP) provides a suitable space mission simulation, we investigated cardiovascular responses of normovolemic and hypovolemic, men and women, to supine and orthostatic stress, induced by head-up tilt (HUT) and upright LBPP, representing standing in lunar, Martian and Earth’s gravities. Methods Six men and six women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thirty-four young adults (19 men and 15 women, 8 Asian, 1 Hispanic, and 25 white) participated in 39 studies, conducted over three years. These original studies were designed to document cardiovascular effects of lower body positive pressure (LBPP) applied to subjects in a standing position (Evans et al, 2013 ; Kostas et al, 2014 ; Zhang et al, 2014 ). Postural controls for each of those studies consisted of data segments collected during the last 10 min of a 30-min supine control period and across 10 min of standing (without LBPP).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-four young adults (19 men and 15 women, 8 Asian, 1 Hispanic, and 25 white) participated in 39 studies, conducted over three years. These original studies were designed to document cardiovascular effects of lower body positive pressure (LBPP) applied to subjects in a standing position (Evans et al, 2013 ; Kostas et al, 2014 ; Zhang et al, 2014 ). Postural controls for each of those studies consisted of data segments collected during the last 10 min of a 30-min supine control period and across 10 min of standing (without LBPP).…”
Section: Methodsmentioning
confidence: 99%
“…However, in some individuals, these compensatory responses are inadequate, and orthostatic intolerance develops ( 6 ). To assess a person's limit of cardiovascular stability during central hypovolemia, head up tilt and lower body negative pressure (LBNP) techniques are employed ( 7 , 8 ). Both are widely used techniques that have shown that there are inter-individual differences in hemodynamic and autonomic responses during central hypovolemia, and that intra-individual responses are highly reproducible ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Central hypovolemia, characterized by a reduction in blood volume within the central circulation ( 1 ), poses significant challenges to the cardiovascular system ( 2 ). The lower body negative pressure (LBNP) technique can be used to assess cardiovascular responses and stability during central hypovolemia ( 3 , 4 ). The application of LBNP shifts the blood from the upper body to the lower body and leads to a decrease in the amount of blood returning to the heart ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%